Phase-feeding strategy for Chlorella vulgaris to enhance biomass and lipid productivity - Haixing, Chang; Qiang, Liao; Qian, Fu; Yun, Huang; Ao, Xia; Yaping, Zheng; Yahui, Sun; Xun, Zhu (International Journal of Agricultural and Biological Engineering, 2017)
A phase-feeding strategy of nutrients based on requirements of Chlorella vulgaris in different physiological phases was examined to maximize the biomass and lipid productivity. This strategy includes reduction of duration in adaption phase (stage-I), enhancement of biomass in growth phase (stage-II) and improvement of lipid productivity in stationary phase (stage-III). The duration of microalgae in adaption phase was reduced from 52 h to 34 h at nitrogen and phosphorus feeding rates of 5.11 mg/(L·d) and 0.54 mg/(L·d), whereas the maximum biomass concentration during growth phase was improved to (4.03±0.25) g/L at nitrogen and phosphorus feeding rates of 20.04 mg/(L·d) and 4.21 mg/(L·d). In stationary and decline phases, a maximum lipid productivity of 132.30 mg/(L·d) was achieved when nutrients supply was stopped at 128 h, which was 28.86 mg/(L·d) higher than that when nutrients supply was stopped at 104 h. This multi-phase cultivation could be a promising strategy for simultaneous enhancement of microalgae biomass and lipid productivity.Keywords: cultivation strategy, lipid productivity, microalgae, nutrients regulationDOI: 10.3965/j.ijabe.20171002.2735Citation: Chang H X, Liao Q, Fu Q, Huang Y, Xia A, Zheng Y P, et al. Phase-feeding strategy for Chlorella vulgaris to enhance biomass and lipid productivity. Int J Agric & Biol Eng, 2017; 10(2): 205–215.